IDENTIFYING SWEAR WORDS UTTERED BY INDONESIA GAMER ON LIVE STREAMING - Arya Wiranda; Thareq Ahmad Alqawwiy; Sholihatul Hamidah Daulay (Rahis Cendekia Indonesia, 2024)
Live streaming sessions on online platforms, focusing on two different genres of games: Clash Royale and DreadOut. Using descriptive qualitative research with content analysis, the study identified and categorized swear words into six types: sexuality, insults, animal-based terms, personal background, intellect-based terms, and English swears. The analysis revealed that the frequency and types of swear words varied depending on the game's nature. In Clash Royale, animal-based terms were predominantly used, while in DreadOut, English swears were more prevalent. Overall, the most frequent swear words across both videos were related to animal-based terms, and English swears, suggesting that gamers adapt their language based on emotions and game environments. The study sheds light on the dynamics of language use in online gaming communities and highlights the role of swear words as expressions of emotion and intensity during gameplay. Further research could explore the psychological and social implications of swearing in gaming contexts and strategies for promoting responsible language use among gamers.